A short history of dinosaurian osteocytes. - Reid, R. E. H. (Robin) (Bernard Price Institute for Palaeontological Research, 1997)
A recent supposed discovery of dinosaurian osteocytes by Fukuda and Obata ( 1993) ignored earlier records from more than 20 dinosaurs, dating back 150 years. Some of the bodies they identified as osteocytes are also more likely to represent chondrocytes.
Main article
Keywords: Bone histology, osteocytes.